Managing the Effectiveness of Teaching Boys Aged 10 Mawashi-Geri (Roundhouse Kick) Technique in Kyokushin Karate - Marchenko, Svitlana; Taranenko, Oleksandr (Physical Education Theory and Methodology, 2020)
The objective of the study was to substantiate the influence of selected independent variables for building optimal models of teaching a series of tasks aimed at motor skills development in boys aged 10. Materials and methods. The study involved 32 boys aged 10. The children and their parents were informed about all the features of the study and gave their consent to participate in the experiment. To achieve the objective set, the following research methods were used: study and analysis of scientific and methodological literature; pedagogical observation, timing of learning tasks; pedagogical experiment, methods of mathematical statistics, methods of mathematical experiment planning. In the process of teaching, a method of algorithmic instructions was used. Results. The effect size of the factor varied from series to series. The calculated Cochran's criterion showed that all the groups of experimental data were obtained from the same population. It was found that the variances do not differ for the selected significance level of 0.05. Each independent variable (X1, X2, X1X2) plays a role in changing the indicator of proficiency in the Mawashi-geri-jodan (roundhouse kick). The constructed mathematical models adequately describe the obtained data. The calculated regression coefficients are statistically significant (Fр < Fkр), which means that the regression model is effective. Throughout the experiment, the independent variable Х1 “number of sets” had a constant positive effect on the target feature (Y). The percentage contribution in the first series of learning tasks was 59.3%, in the second – 88.6%, in the third – 56%, in the fourth – 93.9%, in the fifth – 81.3%, in the sixth – 69.62%. The independent variable Х2 “rest interval” has a negative effect in the first series – 25.9%, in the second series – 10.6%, in the fifth – 9.9%, in the sixth – 13.1%. A positive effect of the first-order interaction (X1X2) was observed in the third series – 29.1%, the fifth – 8.9%, the sixth – 17.28%. Conclusions. The optimal combinations of conditions for the series of tasks when teaching boys aged 10 the Mawashi-geri-jodan (roundhouse kick) are the following: series 1 – 3 sets, rest interval 60 s; series 2 – 3 sets, rest interval 60 s; series 3 – 3 sets, rest interval 120 s; series 4 – 3 sets, rest interval 60–120 s; series 5 – 3 sets, rest interval 120 s; series 6 – 3 sets, rest interval 120 s.